Diploastrea heliopora Sr/Ca and δ18O records from northeast Luzon, Philippines: An assessment of interspecies coral proxy calibrations and climate controls of sea surface temperature and salinity. (30th April 2017) - Ramos, R. D.; Goodkin, N. F.; Siringan, F. P.; Hughen, K. A.
Abstract: The Indo‐Pacific coral Diploastrea heliopora reveals regional multidecadal‐ to centennial‐ scale climate variability using coral carbonate δ 18 O (δ 18 Oc ) as a combined proxy for sea surface temperature (SST) and sea surface salinity (SSS). However, to assess the coral's full potential in resolving climatic events, an independent SST proxy would be more advantageous. We examined both Sr/Ca and δ 18 O of Diploastrea against an adjacent Porites lobata core collected from northeast Luzon, Philippines. Winter Sr/Ca data from Diploastrea show a significant correlation to SST ( r = −0.41, p < 0.05, (root‐mean‐square of the residual) RMSR = 0.81°C) and provide a proxy with similar sensitivity as Porites ( r = −0.57, p < 0.05, RMSR = 0.62°C). An interspecies SST record is shown to be robust and used for a reconstruction of the Pacific Decadal Oscillation during boreal winter ( r = −0.70, p = 0.02). While we were unable to generate a robust Diploastrea δ 18 O‐SSS calibration at interannual timescale, the freshening trend toward the present, commonly observed in the region, is qualitatively captured in Diploastrea δ 18 O. Comparison with Porites δ 18 O and instrumental SSS records shows that the magnitude of freshening is consistent between coral species. Wet and dry season Porites δ 18 O provide support for the relative influence of El Niño–Southern Oscillation events and local precipitation to SSS variability at our site. The multiproxy, multispecies approach of this study further strengthens the evidence for Diploastrea as an alternate climate archive in the Indo‐Pacific region and seals its potential in helping resolve less understood global‐scale climate phenomena. Key Points: Diploastrea heliopora and Porites lobata winter Sr/Ca‐SST calibration are robust and allow for a reconstruction of the PDO Diploastrea heliopora interannual δ 18 Oc ‐SSS records a freshening trend, consistent with Porites lobata δ 18 Oc and instrumental SSS The multiproxy multicoral approach of this study further strengthens the evidence for Diploastrea as an alternate climate archive